Indaziflam: Leaching and control of urochloa plantaginea in applications on coffee litter with different rainfall simulations - da Silva, Paulo Vinicius; Dos Santos, Mayck José; Tronquini, Sergio Mateus; Giraldeli, Ana Ligia; Dias, Roque de Carvalho [UNESP]; Inácio, Estela Maris; Monquero, Patricia Andrea (My University, 2020)
Coffee litter and the rain that occurs after the application of pre-emergence herbicides impact on their leaching and weed control effectiveness. The objective of this study was to evaluate the leaching and control effectiveness of indaziflam, applied on coffee litter, and under simulations of different amounts of rainfall. Two experiments in greenhouse were conducted with the application of indaziflam (0.1 kg of active ingredient-a.i.-ha-1), in a com-pletely randomized design. The first involved the leaching of the herbicide using Urochloa plantaginea as a bioindicator, in a 8 x 4 factorial arrangement, with eight depths in the PVC column (0-0.05; 0.05-0.1; 0.1-0.15; 0.15-0.2; 0.2-0.25; 0.25-0.3; 0.3-0.35; 0.35-0.4 m) and four amounts of straw (0; 1; 3 and 5 t ha-1), this factor was isolated for rainfall simulations (10, 20 and 40 mm). The second experiment tested the effectiveness in controlling U. plantaginea, in a 4 x 3 factorial arrangement, with four amounts of litter (0; 1; 3 and 5 t ha-1) and three amounts of rainfall (10, 20 and 40 mm). Both experiments had four repetitions and controls without application of the herbicide. In leaching, a greater effect of indaziflam was found at a depth of 0-0.05 m, and the higher the simulated rainfall, the greater the phytotoxicity observed in U. plantaginea, with 39.75%, 52.50% and 92.06%, for rainfall amounts of 10, 20 and 40 mm, respectively. U. plantaginea showed high susceptibility to control by the herbicide indaziflam, and the lowest control, 82%, was observed when indaziflam was applied on 5 t ha-1 with simulation of rainfall at 10 mm. The increase in the amount of litter on the soil surface, combined with lower amounts of rainfall can reduce the leaching of indaziflam and the control of U. plantaginea.
Keywords: Alexandergrass; Coffee plantation; Pre-emergence; Transport